New insights into the role of dislocation engineering in N-type filled skutterudite CoSb3. Issue 43 (23rd October 2019) - Liu, Zihang; Meng, Xianfu; Qin, Dandan; Cui, Bo; Wu, Haijun; Zhang, Yang; Pennycook, Stephen J.; Cai, Wei; Sui, Jiehe
Abstract : The critical role of dislocation arrays, introduced by a liquid phase compaction process, on electron and phonon transport behavior is thoroughly elucidated. Abstract : Dislocation engineering has recently been recognized as an effective approach to develop high-performance thermoelectric materials. However, to date, the nature of dislocation engineering for performance enhancement has remained elusive in bulk materials, because the introduction of dislocations is normally accompanied by the change of the material's composition that leads to more variables in comparing and analyzing transport properties. Here, taking the Yb filled skutterudite CoSb3 as a typical example, we first clearly unveil the critical role of dislocation arrays, introduced by a liquid-phase compaction process, on electron and phonon transport behavior. Due to the fact that the dislocation width is comparable with the electron mean free path, dislocation arrays effectively screen the low-energy carriers and induce the carrier filtering effect, which leads to a remarkable enhancement of both the Seebeck coefficient and the power factor. More importantly, beyond the classical theory that the reduction of thermal conductivity is merely caused by the targeted phonon scattering via dislocations, we first discover that dislocation arrays result in lattice softening and strengthening bond anharmonicity simultaneously, both of which significantly impede the normal heat conduction process. Benefitting from dislocation engineering coupled with tuning the Yb filling fraction, we demonstrate a high thermoelectric figure of merit ZT of 1.54 at 873 K among the n-type single-filled skutterudite CoSb3 . Our work not only highlights the promising prospect of Yb filled skutterudite CoSb3 for energy harvesting but also first clearly unveils the critical role of dislocation engineering for ZT enhancement.